PENGEMBANGAN MEDIA PEMBELAJARAN MAGIC POCKET TREE DALAM MENINGKATKAN MINAT BELAJAR SISWA: (Studi kasus MI Nidzomiyah Sentul Jombang) - Waton, Muhammad Nasrul; Mubarokah, Ayu Lailatul (Prodi PGMI Institut Agama Islam Bani Fattah Jombang, 2022)
The development of the Magic Pocket Tree learning media was carried out as an effort to assist teachers in increasing students' interest in learning. The background of this research is the use of learning media that is still not diverse, namely only using makeshift media such as blackboards, textbooks/LKS and others. The use of monotonous learning media makes children bored so that to support learning to be more interesting it is necessary to have a variety of learning media and children are interested in the learning media. Research conducted by researchers using the research and development (R&D) method of the Borg and Gall model was carried out in six stages, namely 1) preparation and data collection stage 2) development stage 3) product trial stage 4) revision stage 5) trial stage field 6) dissimilation and implementation stages. Data collection techniques used were interviews, observations, tests, and questionnaires. Quantitative and qualitative data were analyzed using a Likert scale.The focus of the research in writing this thesis is 1) how is the process of developing Magic Pocket Tree learning media in class IV Fiqh subjects at MI Nidzomiyah Sentul 2) how is the feasibility level of Magic Pocket Tree learning media in class IV Fiqh subjects at MI Nidzomiyah Sentul 3) whether Can Magic Pocket Tree learning media development products increase the learning interest of fourth grade students at MI Nidzomiyah Sentul? The application of the development of learning media is given to students so that students further increase their interest in learning. From the calculation results it can be seen that the development of this learning media can increase the effectiveness and interest of students' learning when used in the teaching and learning process in schools and this learning media is feasible to be used as additional learning so that learning activities can run smoothly and effectively. Learning media in the form of a plywood board with questions in its pocket has been developed and tested through a media expert validation questionnaire with an average assessment of 84.00% categorized as very feasible, a material validation questionnaire with an average assessment of 94.00% very feasible.